2003
DOI: 10.1037/0278-7393.29.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Concave utility, transaction costs, and risk in measuring discounting of delayed rewards.

Abstract: Research has consistently found that the decline in the present values of delayed rewards as delay increases is better fit by hyperbolic than by exponential delay-discounting functions. However, concave utility, transaction costs, and risk each could produce hyperbolic-looking data, even when the underlying discounting function is exponential. In Experiments 1 (N = 45) and 2 (N = 103), participants placed bids indicating their present values of real future monetary rewards in computer-based 2nd-price auctions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 29 publications
1
44
0
5
Order By: Relevance
“…In other experiments they reported an amount that they would be willing to receive at the time of the session in lieu of the delayed reward. Although in theory these procedural variations could lead to different responses, Kirby and Santiesteban (2002) found no differences in the discount rates that they generated.On each trial, the participant's reported present value of the delayed reward was entered into a sealed-bid, second-price auction. In some experiments participants bid against other participants (Kirby, 1997;1998), and in other experiments they bid against the computer (Kirby, 1998;Kirby & Santiesteban, 2002).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…In other experiments they reported an amount that they would be willing to receive at the time of the session in lieu of the delayed reward. Although in theory these procedural variations could lead to different responses, Kirby and Santiesteban (2002) found no differences in the discount rates that they generated.On each trial, the participant's reported present value of the delayed reward was entered into a sealed-bid, second-price auction. In some experiments participants bid against other participants (Kirby, 1997;1998), and in other experiments they bid against the computer (Kirby, 1998;Kirby & Santiesteban, 2002).…”
mentioning
confidence: 92%
“…Although in theory these procedural variations could lead to different responses, Kirby and Santiesteban (2002) found no differences in the discount rates that they generated.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Such measures have occasionally been used to quantify model fit in the delay-discounting literature (two instances are Kirby &Santiesteban, 2003, using RMSE, andMadden et al, 1997, using SSE). In addition, a variety of other approaches have been recommended as methods for evaluating nonlinear regression models based on model generalizability rather than goodness-of-fit, such as the Akaike information criterion (AIC) and the Bayesian information criterion (BIC) (Burnham & Anderson, 2002;Forster, 2000;Pitt & Myung, 2002;Zucchini, 2000).…”
Section: An Empirical Demonstration Of the Problematic Nature Of R 2 mentioning
confidence: 99%
“…O escore de desconto do futuro foi obtido a partir das respostas individuais a nove questões sobre preferência por receber valores menores em um prazo mais curto ou maiores em um prazo mais longo (por exemplo, "Você prefere receber R$ 34,00 amanhã ou R$ 35,00 em 186 dias?"). O procedimento de cálculo do desconto foi baseado numa equação de função hiperbólica, denominado valor k (Kirby & Santiesteban, 2003, Wilson & Daly, 2004. Esse instrumento não apresenta normalização para respondentes brasileiros, mas tem sido utilizado em vários estudos mostrando adequação de construto (Ferreira, 2009;Ornellas, 2010;Howat-Rodrigues, 2010).…”
Section: Instrumentosunclassified